Functional evolution of the colony‐stimulating factor 1 receptor (CSF1R) and its ligands in birds - Hume, D.A.; Gutowska‐Ding, M.W.; Garcia‐Morales, C.; Kebede, A.; Bamidele, Oladeji; Trujillo, A.V.; Gheyas, Almas A.; Smith, J. (Oxford University Press, 2020)
Macrophage colony-stimulating factor (CSF1 or M-CSF) and interleukin 34 (IL34) are secreted cytokines that control macrophage survival and differentiation. Both act through the CSF1 receptor (CSF1R), a type III transmembrane receptor tyrosine kinase. The functions of CSF1R and both ligands are conserved in birds. We have analyzed protein-coding sequence divergence among avian species. The intracellular tyrosine kinase domain of CSF1R was highly conserved in bird species as in mammals but the extracellular domain of avian CSF1R was more divergent in birds with multiple positively selected amino acids. Based upon crystal structures of the mammalian CSF1/IL34 receptor-ligand interfaces and structure-based alignments, we identified amino acids involved in avian receptor-ligand interactions. The contact amino acids in both CSF1 and CSF1R diverged among avian species. Ligand-binding domain swaps between chicken and zebra finch CSF1 confirmed the function of variants that confer species specificity on the interaction of CSF1 with CSF1R. Based upon genomic sequence analysis, we identified prevalent amino acid changes in the extracellular domain of CSF1R even within the chicken species that distinguished commercial broilers and layers and tropically adapted breeds. The rapid evolution in the extracellular domain of avian CSF1R suggests that at least in birds this ligand-receptor interaction is subjected to pathogen selection. We discuss this finding in the context of expression of CSF1R in antigen-sampling and antigen-presenting cells.